2018
DOI: 10.2478/jok-2018-0047
|View full text |Cite
|
Sign up to set email alerts
|

Alternative fuel in the combustion process of combustion engines

Abstract: The article analyses the impact of emulsified fuel, containing H2O2 hydrogen peroxide, on the emissions of nitrogen oxides and diesel engine smoke. The process of forming toxic components in exhaust gases of reciprocating engines during the engine operation, and the relationship that specifies the hydrogen peroxide decomposition process were presented. The research was carried out with the use of fuel containing 30%, 20% and 10% of hydrogen peroxide. The concentration courses of the nitric oxide (NO) and nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In Poland, the subject of research on the impact of supplying internal combustion engines with emulsion fuels was dealt with by Jankowski [8][9][10][11]. As a result of research done by Jankowski showed that microemulsions retain the usability of the emulsion while minimizing the negative features of this type of fuel.…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, the subject of research on the impact of supplying internal combustion engines with emulsion fuels was dealt with by Jankowski [8][9][10][11]. As a result of research done by Jankowski showed that microemulsions retain the usability of the emulsion while minimizing the negative features of this type of fuel.…”
Section: Introductionmentioning
confidence: 99%
“…Droplets in the spray have different diameters, depending on the discharge conditions and fuel properties. From the point of view of the econo-mics of the combustion engine operation and the emission of toxic exhaust components, differences in the size of droplets should be within a narrow range [4,5]. To determine the quality of the fuel spray, two substitute diameters Sauter (D 32 ) and Herdan (D 43 ) were selected, the first of which refers to heat transfer and the second − to combustion processes.…”
Section: Introductionmentioning
confidence: 99%